Gender Disparities in the Kenyan Labour Market: Implications for Poverty Reduction (Nordic Journal of African Studies, 2002)
Parts one and two of this paper deal with conceptual issues and focus on gender mainstreaming into investment activities for increased women's employment and poverty reduction. The central argument here is that the mainstreaming of a gender perspective into investment activities is necessarily a long-term process which involves the integration of gender issues in all national and sectoral policies and programmes. The key to gender mainstreaming is to make the process a collective responsibility. Some of the essential steps in this process are the production of gender disaggregated data, the establishment and strengthening of gender management systems, the commitment of senior management personnel to the goal of gender equality as a reflection of attitudinal and behaviour change at personal and institutional levels. The discussion in part three brings to the fore the issue of women's education and training. Available data show gender and regional disparities in education and training at primary, secondary and tertiary levels. These data indicate women's limited access to formal education and lower adult literacy rates which undermine their capacity to participate in the formal and informal labour market on an equal basis with men. Part four shows the link between women's education, employment and poverty reduction. The analysis of gender participation in different sectors of the economy revealed some important patterns and trends. These include the fact that female labour force participation in the modern sector has remained below 30% over the last several years compared to men who hold a disproportionately larger share of the modern sector jobs. The majority of women are employed in the education and informal sectors. Those who work in the agricultural sector are usually engaged as casuals. Women's overall lower level of education, limited skills, and access to productive, resources, heavy domestic workload, cultural attitudes and segregation of the labour market are some of the factors associated with their limited participation in the modern sector. Gender representation in the Kenyan civil service also shows gross under-representation of women in top management and policy-making positions. This gender disparity calls for an Affirmative and/or Positive Action to deal not only with increasing women's participation in public and private sector institutions at all levels but also address the twin issue of women's entitlements and cultural barriers which are at the root of their poverty and powerlessness. The low budgetary allocations to women's programmes also reflect lack of political will, improper targeting and non-involvement of women in priority setting.